The Figure of Ophelia in Expressionist Poetry: German and Czech Comparison - Malý, Radek (Porównania, 2020)
The study deals with the rendition of the figure of Ophelia in Czech modern poetry in comparison with the poetry of European Expressionism. The image of Ophelia’s aesthetic death from Shakespeare’s drama Hamlet has influenced and inspired a whole range of artworks. It strongly reverberated in German Expressionist poetry, especially that by Georg Heym, Gottfried Benn and Georg Trakl. The Czech poets who approached this topic in the spirit of Expressionism include Jan Skácel, Vladimír Holan and Jiří Orten. The study further addresses these works in the light of the Ophelia complex as defined by Bachelard.